Biodiesel Waste Cooking Oil is Environmentally Friendly Alternative Fuels and More Feasible than Fossil Fuels - Prasutiyon, Hadi; Fatallah, Aguk Zuhdi Muhammad (International Journal of Marine Engineering Innovation and Research, 2025)
The use of diesel engines is increasing at the moment, the other hand, supplies of petroleum base diesel oil in the market decreasing. Therefore we need alternative fuels to use as supplement fuel for diesel engines. Biodiesel processing can be done with the process of esterification and transesterification. Biodiesel is processed from used cooking oil can be done only by the transesterification process. Ester transesterification is the process of converting into esters in another form by reacting carboxylic esters and alcohols with an alkaline catalyst (NaOH), in processing biodiesel transesterification process is the process of converting triglycerides of cooking oil into methyl or ethyl ester as biodiesel. According to various studies, biodiesel derived from waste cooking oil proved to be more environmentally friendly fuels than the results are known and used today. Nitrogen Monoxide emission levels (NOx) in the biodiesel from used cooking oil to produce emissions 12% lower than emissions produced by diesel oil. Another advantage, the exhaust emissions of the unburned form of carbohydrates produced biodiesel used cooking oil turned out to be 25% lower than on diesel oil. The diesel engine durability test, performance analysis, analysis of the degree of damage is indicated by the metal content in lubricants, and test the properties of each lubricating it can be some conclusions as follows.